Penerapan Full Day School Terhadap Pembinaan Akhlakul Karimah Siswa - Miftahul Aula Sa`adah; Mahmudah Mahmudah (Al-Mudarris, 2019)
Cultivation and guidance morals in schools is very necessary, because progress in the field of science and technology has a positive and negative impact on student development. Nowadays moral decline by students raises unrest for families, schools and communities. Through the full day school program, it is hoped that the school will not only become a place for transfer of knowledge but also as a forum for guidancing morality for students. The approach used in this research is field research. Data collectiontechniques through observation, interviews, and documentation. Then the data is processed using a qualitative descriptive analysis approach. The results obtained in this study indicate that the application of full day school to the development of students' morality in SMA Ukhuwah Banjarmasin is carried out through intracuricular activities and extracurricular activities. Intracuricular activities are carried out through teaching and learning processes and Islamic personal development. The extracurricular activities include scouting, sports and arts, and Ramadhan tarhib. Supporting factors in the formation of student morals are a curriculum that is compatible with the integration of Islamic values, quality human resources, supporting infrastructure facilities, and active involvement and support from parents of students. The inhibiting factors are the students' environmental factors and funding factors.